TERAPI DINGIN EEFEKTIF MENURUNKAN NYERI STERNOTOMY SAAT LATIHAN NAPAS DAN BATUK EFEKTIF - Chatarina Setya Widyastuti (Universitas Jenderal Achmad Yani Yogyakarta, 2013)
Background: Patients after coronary bypass surgery will experience pain as a result of sternotomy wounds, especially during deep breathing and coughing. They will always be given the breathing exercises and cough effectively to assist recovery and prevent respiratory complications. Pain can be reduced by cold therapy. Objective: purpose this Evidence Based Practice is determine the effectiveness of cold therapy in reducing sternotomy pain during breathing exercises and coughing. Methods: Participants (n = 6), in a randomized crossover trial, applied a frozen gel pack to their sterna incision dressing before performing deep breathing and coughing (DB & C) exercises. Pain scores from 0 to10 at rest were compared with pain scores post DB &C with and without the gel pack. Participants were also asked to describe their sensations with the frozen gelpack, as well as their preferences for gel pack application. Results: The analysis of differences in pain scores between pre- and post-application of the gel pack is significant reduce 0,5 -0,7. Pain scores post DB &C without the gel pack is increase 1,4 -1,5. All 6 (100%) participants would reapply the gel pack in the future. Conclusion: cold therapy is effective reducing pain during deep breathing exercise and coughing from moderate become mild. Application of cold therapy is an affordable, low risk and can be easily integrated in nursing practice. Keywords: Cold therapy, CABG, pain, sternotomy